Meta-Analysis: The Effectiveness of Acupucture in Reducing Pain and Improving Quality of Life in Patients with Low Back Pain - Winahyu, Frannesty Estu; Prasetya, Hanung; Murti, Bhisma (Indonesian Journal of Medicine, 2022)
Background: In Indonesia, low back pain is a common health problem that can interfere with a person's productivity in carrying out activities due to the manifestations of the pain it causes. Acupuncture therapy is one of the complementary treatments that is quite effective in reducing the intensity of low back pain. This study aims to estimate the effectiveness of acupuncture therapy to reduce pain and improve quality of life in patients with low back pain.Subjects and Method: This study is a systematic review and meta-analysis with PICO, Population: Low back pain patients, Intervention: Acupuncture therapy, Comparison: No acupuncture therapy, Outcome: Pain reduction and quality of life improvement. It was measured using the Oswestry Disability Index. The article search process was carried out between 2006-2022 using 3 databases, including Google Scholar, PubMed, and Science Direct. The keywords used in the database search were “acupuncture” AND “oswestry disability index” AND “quality of life” AND “low back pain”. The inclusion criteria for full text articles using a Randomized Controlled Trial (RCT) study design by including the results of the study in the form of the number of respondents, the mean and standard deviation (SD) values, for articles using English and Indonesian. Articles that have met the requirements are analyzed using the RevMan 5.3 application.Results: There are 9 articles that meet quantitative requirements and are divided into 2 categories according to independent variables with a Randomized Controlled Trial (RCT) study design originating from Spain, Australia, South Korea, Brazil, Germany and England, which were carried out in a meta-analysis in this study. Meta-analysis of 7 articles showed estimates that acupuncture therapy was effective in reducing pain in LBP patients. Patients experienced a decrease in pain 0.32 units higher than those who were not given acupuncture therapy (SMD = 0.32; 95% CI= -0.46 to -0.17; p <0.001). Meanwhile, a meta-analysis of 9 articles showed the estimation of the effect of effective acupuncture therapy on improving the quality of life in LBP patients. Patients experienced an improvement in quality of life 0.52 units higher than those who were not given acupuncture therapy (SMD = 0.52; 95% CI= 0.22 to 0.81; p= 0.006).Conclusion: Acupuncture therapy is effective in reducing pain and improving the quality of life of LBP patients. Keywords: acupuncture, low back pain, quality of life, oswestry disability index, meta-analysisCorrespondence: Frannesty Estu Winahyu. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java. Email: frannestyestuwinahyu@gmail.com. Mobile: +6285228783882.Indonesian Journal of Medicine (2022), 07(03): 313-325https://doi.org/10.26911/theijmed.2022.07.03.08